Fusarium graminearum GGA protein is critical for fungal development, virulence and ascospore discharge through its involvement in vesicular trafficking. (14th November 2022) - Sun, Fengjiang; Zhang, Ruotong; Li, Tiantian; Zhang, Liyuan; Chen, Xiaochen; Liang, Yuancun; Chen, Lei; Zou, Shenshen; Dong, Hansong
Abstract: Vesicular trafficking is a conserved material transport process in eukaryotic cells. The GGA family proteins are clathrin adaptors that are involved in eukaryotic vesicle transport, but their functions in phytopathogenic filamentous fungi remain unexplored. Here, we examined the only GGA family protein in Fusarium graminearum, FgGga1, which localizes to both the late Golgi and endosomes. In the absence of FgGga1, the fungal mutant exhibited defects in vegetative growth, DON biosynthesis, ascospore discharge and virulence. Fluorescence microscopy analysis revealed that FgGga1 is associated with trans ‐Golgi network (TGN)‐to‐plasma membrane, endosome‐to‐TGN and endosome‐to‐vacuole transport. Mutational analysis on the five domains of FgGga1 showed that the VHS domain was required for endosome‐to‐TGN transport while the GAT 167‐248 and the hinge domains were required for both endosome‐to‐TGN and endosome‐to‐vacuole transport. Importantly, the deletion of the FgGga1 domains that are required in vesicular trafficking also inhibited vegetative growth and virulence of F. graminearum . In addition, FgGga1 interacted with the ascospore discharge regulator Ca 2+ ATPase FgNeo1, whose transport to the vacuole is dependent on FgGga1‐mediated endosome‐to‐vacuole transport. Our results suggest that FgGga1 is required for fungal development and virulence via FgGga1‐mediated vesicular trafficking, and FgGga1‐mediated endosome‐to‐vacuole transport facilitates ascospore discharge in F. graminearum .